Anti-citrullinated alpha enolase antibodies, interstitial lung disease and bone erosion in rheumatoid arthritis. (14th February 2018) - Alunno, Alessia; Bistoni, Onelia; Pratesi, Federico; La Paglia, Giuliana Maria Concetta; Puxeddu, Ilaria; Migliorini, Paola; Gerli, Roberto
Abstract: Objectives: RA is an articular chronic inflammatory disease that in a subgroup of patients can also present with extra-articular manifestations (EAMs). Despite intense investigation on this topic, reliable biomarkers for EAMs are lacking. In recent years several ACPAs, including those targeting anti-citrullinated alpha enolase peptide-1 (anti-CEP-1), have been identified in patients with RA. Data about the ability of anti-CEP-1 to predict the development of erosive disease are confliciting and no evidence concerning their possible association with EAMs in RA is currently available. The aim of this study was to investigate the prevalence and significance of anti-CEP-1 with regard to the association with erosive disease and EAMs in a large cohort of patients with RA. Methods: Anti-CCP and anti-CEP-1 antibodies have been assessed on serum samples of RA patients, healthy donors and patients with SpA using commercially available ELISA kits. Results: Anti-CEP-1 antibodies are detectable in over 40% of RA patients and are associated with erosive RA and with RA-associated interstitial lung disease ( ILD). Conclusion: Anti-CEP-1 antibodies may represent a useful biomarker for RA-associated ILD and erosive disease to be employed in clinical practice.